2017
DOI: 10.1177/2057047317732350
|View full text |Cite
|
Sign up to set email alerts
|

Alliance of antagonism: Counterpublics and polarization in online climate change communication

Abstract: Debates around climate change are a prominent example of polarized online communication. We examine the German climate hyperlink network and evaluate the degree to which it is shaped by mainstream and skeptical views. By combining the theoretical frameworks of the networked public sphere and counterpublics, we describe the relation between publics and counterpublics and discuss the role of hyperlinks in delineating communities. Our analysis of blogrolls and link lists shows the debate’s structures to be polari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(35 citation statements)
references
References 53 publications
3
30
1
1
Order By: Relevance
“…At the same time, the presence of these competitive narratives of solidarity with migrants versus the narratives of migrant otherness provides some evidence for a possible polarisation of the Facebook audience. This suggestion can be supported by results of previous studies finding that social media audiences are considerably polarised based on their ideological stances [49].…”
Section: Discussionsupporting
confidence: 70%
“…At the same time, the presence of these competitive narratives of solidarity with migrants versus the narratives of migrant otherness provides some evidence for a possible polarisation of the Facebook audience. This suggestion can be supported by results of previous studies finding that social media audiences are considerably polarised based on their ideological stances [49].…”
Section: Discussionsupporting
confidence: 70%
“…Next to that, there are various communities of bloggers that support the scientific consensus on climate change ("climate mainstream bloggers") [7], for example climate scientists that blog to correct misinformation on climate change [11]. Previous studies showed that persistent polarization around climate change manifests itself in online communities and topics [7], hyperlinking [12,13], bloggers' operationalization of journalistic norms [11], discursive constructions of reality [14,15], and interaction strategies in comment threads [16] of the climate change blogosphere. Importantly, to date, little research has focused on audiences in the climate change blogosphere.…”
Section: Introductionmentioning
confidence: 99%
“…Computational methods represent a set of tools for the analysis of digital traces which are increasingly being used in the interdisciplinary study of communication and media. Examples include network and link analysis supported by crawlers and application programming interfaces (APIs; Himelboim et al., 2013; Kaiser and Puschmann, 2017), sentiment analysis (Ceron et al., 2014; Young and Soroka, 2012), the use of supervised machine learning methods for automated content analysis (Schwartz and Ungar, 2015; Van Atteveldt et al., 2008) and topic modelling (Jacobi et al., 2016; Rauchfleisch, 2017).…”
Section: Introductionmentioning
confidence: 99%